Las rentas agrarias y rurales en Extremadura - Gurría Gascón, José Luis; Nieto Masot, Ana; Hernández Carretero, Ana María (Geographicalia, 2014)
Extremadura is a largely rural region, in fact twenty largestcities agglutinate only half of the population. In the last two or threedecades profound changes have occurred which marked the transitionfrom a subsistence agricultural economy to a competitive service economy,which has affected both the cities and, more attenuated, the ruralareas. These changes, however, were not sufficient to explain the stabilityof the population in rural areas, still quite dependent on the agriculturalsector unable to produce the development of these areas. However, under the politics and economic situation of the last decades,the rural population has managed to generate a series of mixed multisectoralincome and new dynamics, based on mobility, which allowedan increase of level of living and the population stability.